Neurotrophic effects of perfluorocarbon emulsion gel: a pilot study - Isaacs, Jonathan; Friebe, Ilvy; Mallu, Satya; Bachman, Keith (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
Background Positive neurotrophic effects of hyperbaric oxygen treatment may be more easily achieved by applying a Perflourocarbon (PFC) emulsion gel to the repair site. PFCs are halogen substituted carbon oils with unique oxygen transport potentials that are capable of increasing oxygen availability in local tissues. The purpose of this study was to determine if the application of a PFC emulsion to a repaired nerve would improve recovery.Materials and methods The left tibial nerve of 21 immature female Sprague-Dawley rats was transected, immediately repaired, and then circumferentially coated with PFC gel (Group A, n = 7), PFC-less gel (Group B, n = 7), or nothing (suture only, Group C, n = 7). At eight weeks post surgery, electrophysiological testing and histological and morphological analysis was performed.Results No statistically significant differences between experimental groups were found for muscle size and weight, axon counts, or nerve conduction velocity. Group A had a significantly smaller G-ratio than Groups B and C (p < .0001).Conclusion Overall results do not indicate a functional benefit associated with application of a PFC emulsion gel to rodent tibial nerve repairs. A positive effect on myelination was seen.
Keywords: Perfluorocarbons; Nerve Repair; Nerve Regeneration